The Effect of A Self-Management Support Program on The Achievement of Goals in Diabetic Foot Care Behaviors in Indonesian Diabetic Patients - Kurniwawan, Titis; Sae-Sia, Wipa; Maneewat, Khomapak; Petpichetchian, Wongchan (Nurse Media Journal of Nursing, 2011)
Introduction: Diabetic foot care behaviors (DFCB) are a fundamental component of the prevention of diabetic foot complications. This quasi-experimental study aimed to examine the effect of a self-management support program on the achievement of DFCB goals in Indonesian diabetic patients.Method: Thirty-five subjects were recruited from the diabetic unit of a district hospital in West Java, Indonesia. The subjects received a five-week diabetic foot care self-management (SM) support program. This program consisted of three sequential phases based on the self-management method proposed by Kanfer and Gaelick-Buys (1991): self-monitoring, self-evaluation, and self-reinforcement. The strategies used in this program consisted of individual foot care education, goal setting and action planning, and brief weekly counseling and follow-ups. The goals achieved from the second to the fourth weeks were evaluated weekly by phone call follow-ups with a face-to-face interview evaluation in the fifth week. The level of goal achievement was determined by counting the number of successfully implemented actions based on the subject’s action plans. The actual goal achievement was then classified into three levels: goal completely achieved, goal partially achieved and no behavioral change (no action) at all. Results: Most of the subjects (94.3%) were able to completely achieve their first week goals whereas only approximately two-thirds of the subjects were able to completely achieve their goals in the second to the fourth weeks. Throughout the program, less than half of the subjects (42.9%) completely achieved all four weekly goals although only one subject (2.9%) was unable to achieve any of the weekly goals. The most improved DFCB component in each of the first to fourth weeks was foot hygiene, footwear, toenail care and a combination of foot hygiene and footwear, respectively.  Conclusion: This SM support program effectively improved the Indonesian diabetic patients’ foot care behaviors. Therefore, nurses can apply this program in practice in enhancing DFCB in order to prevent diabetic foot ulceration.Keywords: Diabetic foot care behaviors, self-management, diabetic patients